Change from standard form to slope intercept form
 Rewrite the equation in slope intercept form.                         x-y=1y=x+1y=-x+1y=-x-1 y=x-1 Rewrite the equation in slope intercept form.                         x+y=5y=x+5y=-x-5y=-x+5 y=x-5 Rewrite the equation in slope intercept form.                         x- y = 7y=x+7y=x-7y=-x-7 y=-x+7 Rewrite the equation in slope intercept form.                         2x+ y= 4y=2x+4y=-2x+4y=-2x+ 2 y=2x-4 Rewrite the equation in slope intercept form.                         6x+3y=9 y=2x+3 y=-2x-3 y=2x-3 y=-2x+3 Rewrite the equation in slope intercept form.          -8x-4y=12y=2x-3y=-2x+3y=-2x-3y=2x+3 Rewrite the equation in slope intercept form.          -4x-2y=1y=-2x - 2y=-2x - ½y=-x-1 y=x-1 Rewrite the equation in slope intercept form.               x-y=-1y=x+1y=-x+1y=-x-1 y=x-1 Rewrite the equation in slope intercept form.           2x + 4y=-12y=-½x-12y=½x-3y=-½x-3y=2x-12 Rewrite the equation in slope intercept form.    2x+3y=6y=-⅔x+2y=⅔x+2y=-⅔x+6y=-⅔x-2 Rewrite the equation in slope intercept form.    -2x+3y=6y=-⅔x+2y=⅔x+2y=-⅔x+6y=-⅔x-2 Rewrite the equation in slope intercept form.           -2x + 4y=-12y=-½x-12y=½x-3y=-½x-3y=2x-12 Rewrite the equation in slope intercept form.          4x-2y=1y=-2x - ½y=2x - ½y=-x-1 y=x-1 Rewrite the equation in slope intercept form.                         -6x+3y=9 y=2x+3 y=-2x-3 y=2x-3 y=-2x+3 Rewrite the equation in slope intercept form.          -8x + 4y=12y=2x-3y=-2x+3y=-2x-3y=2x+3
Created with That Quiz — a math test site for students of all grade levels.